Organoid models of gastrointestinal cancers in basic and translational research - Lau, Harry Cheuk Hay; Kranenburg, Onno; Xiao, Haipeng; Yu, Jun (Nature reviews. Gastroenterology & hepatology, 2020)
Cancer is a major public health problem worldwide. Gastrointestinal cancers account for approximately one-third of the total global cancer incidence and mortality. Historically, the mechanisms of tumour initiation and progression in the gastrointestinal tract have been studied using cancer cell lines in vitro and animal models. Traditional cell culture methods are associated with a strong selection of aberrant genomic variants that no longer reflect the original tumours in terms of their (metastatic) behaviour or response to therapy. Organoid technology has emerged as a powerful alternative method for culturing gastrointestinal tumours and the corresponding normal tissues in a manner that preserves their genetic, phenotypic and behavioural traits. Importantly, accumulating evidence suggests that organoid cultures have great value in predicting the outcome of therapy in individual patients. Herein, we review the current literature on organoid models of the most common gastrointestinal cancers, including colorectal cancer, gastric cancer, oesophageal cancer, liver cancer and pancreatic cancer, and their value in modelling tumour initiation, metastatic progression and therapy response. We also explore the limitations of current organoid models and discuss how they could be improved to maximally benefit basic and translational research in the future, especially in the fields of drug discovery and personalized medicine. Organoid technology has emerged as a powerful method for studying gastrointestinal cancers. This Review describes organoid models of gastrointestinal cancers, such as colorectal and liver cancer, and discusses how they can be used in basic and translational research in fields such as drug discovery and personalized medicine. Key points Gastrointestinal cancers account for one-third of the total global cancer incidence and mortality; therefore, it is essential to translate knowledge from basic research into health benefits by advancing therapeutics. Preclinical cancer research has been heavily reliant on cell lines and animal models, but both fail to recapitulate the original human tumours. Organoid technology has emerged as a powerful alternative method for culturing gastrointestinal tumours and their corresponding normal tissues in a manner that preserves their genetic, phenotypic and behavioural traits. Organoid models have been used to model tumour initiation, metastatic progression and therapy response of the most common gastrointestinal cancers, including colorectal cancer and liver cancer. Clinical applications of patient-derived organoids are promising, as accumulating evidence has revealed the potential of organoid models in drug discovery, modelling therapy response and personalized medicine. Current organoid models have multiple limitations; therefore, more work is necessary to enable them to maximally benefit basic and translational research in gastrointestinal cancers.